8‐Substituted, syn‐Configured Adenosine Derivatives as Potential Inhibitors of the Enzyme IspE from the Non‐Mevalonate Pathway of Isoprenoid Biosynthesis1. Issue 33 (21st October 2015) - Harder, Michael; Schäfer, Elisabeth; Kümin, Tobias; Illarionov, Boris; Bacher, Adelbert; Fischer, Markus; Diederich, François; Bernet, Bruno
Abstract: The enzymes of the non‐mevalonate pathway for isoprenoid biosynthesis are attractive targets for drugs against various diseases, including malaria. We describe herein the structure‐based design, synthesis, conformational analysis, and biological evaluation of several 8‐brominated or 8‐aminated adenosine derivatives with different substituents at C(5′), targeting the ATP‐adenine binding site of the IspE protein from the non‐mevalonate pathway. An exhaustive conformational analysis of the adenosine derivatives both in solution and in the solid state confirmed the desired syn orientation of the adenine moiety. Despite this favorable pre‐organization for binding to the cofactor pocket, biological evaluation of the inhibitors showed only a very modest inhibitory activity. Abstract : A structure‐based design approach has been used to develop 8‐bromo‐ and 8‐amino‐adenosine‐derived inhibitors with different substituents at C(5′), targeting the ATP‐binding pocket of the enzyme IspE. An exhaustive conformational analysis in the solid state and in solution was performed and the biological activities evaluated. The new adenosine derivatives were found to be weakly binding ligands.